Evaluación a métodos y técnicas de enseñanza aprendizaje utilizada por los docentes de matemática en el módulo cuatro del bloque geométrico de polígonos en los estudiantes del octavo año de educación general básica del instituto superior tecnológico fiscomisional Juan XXIII del cantón Yantzaza, provincia de Zamora Chinchipe, periodo académico 2012-2013. Lineamientos alternativos - Gueledel Sucunuta, Betty Mireya (2015)
The research entitled: "Evaluation methods and techniques of teaching and learning, teachers used in the module Mathematical four geometric block polygons eighth grade students of Basic General Education Higher Technological Institute Fiscomisional John XXIII, the Canton Yantzaza province of Zamora Chinchipe, academic period 2012-2013 "aims to answer the question What is the impact the types of methods and techniques used by math teachers in the teaching-learning process ?, to be a topic of vital importance in During the educational process. The overall objective of this research aims to: evaluate methods and techniques in the teaching-learning process used by teachers of mathematics in four geometric module block polygons students eighth year of General Basic Education Institute of Technology Juan XXIII Fiscomisional Yantzaza Canton province of Zamora Chinchipe, academic period 2012-2013. Among the methods used is the scientific method, the same that provided the necessary elements with which allowed the construction of the thesis project, starting from a problematization, delineation and characterization of the problem that led to the objectives and compliance as well as the development of themes in the literature review, analysis and discussion of the results, the deductive method allowed to know and analyze the general aspects of the learning process in the field of geometry; inductive method using this method the problem was identified and the most relevant and scientific information to strengthen the study, the analytic-synthetic method facilitated the evaluation of research categories, descriptive statistical method was employed in the development of selected field research, in a coherent and logical procedure that allowed the application and collection of information and then make the tabulation of data, statistical tables, graphical representation of the significant facts which provided research. As for the techniques, the survey aimed at teachers and students was used. Among the main results of research of teachers do not use appropriate methods for the study of this topic techniques. Not suitable for classroom teaching activities polygons are used.